Importance of the aromatic structures in volatiles to the in-situ destruction of nascent tar during the volatile-char interactions - Song, Y.; Xiang, J.; Hu, S.; Quyn, D.; Zhao, Y.; Hu, Xun; Wang, Y.; Li, Chun-Zhu (Elsevier, 2015)
This study aims to investigate the importance of aromatic structures in tar to the destruction of tar itself during the volatile-char interactions. The same nascent char was subjected to interactions with two distinctly different volatiles (e.g. coal volatiles and biomass volatiles) at 700-900 °C. The results indicate that the aromatic structures in tar are more reactive with char than the non-aromatic structures, especially at high temperature (e.g. 900 °C). At lower temperatures (< 800 °C), the more aromatic coal tar can form coke on the char surfaces more easily than the more aliphatic biomass tar. At higher temperatures (> 800 °C), the aromatic structures in tar are cracked and/or reformed into gases through interaction with the char; the aromatic structures from biomass can be reformed over char more easily than those from coal.